An Australian survey of parent involvement in intervention for childhood speech sound disorders. (28th December 2018) - Sugden, Eleanor; Baker, Elise; Munro, Natalie; Williams, A. Lynn; Trivette, Carol M.
Abstract: Purpose : To investigate how speech-language pathologists (SLPs) report involving parents in intervention for phonology-based speech sound disorders (SSDs), and to describe the home practice that they recommend. Further aims were to describe the training SLPs report providing to parents, to explore SLPs' beliefs and motivations for involving parents in intervention, and to determine whether SLPs' characteristics are associated with their self-reported practice. Method : An online survey of 288 SLPs working with SSD in Australia was conducted. Result : The majority of SLPs (96.4%) reported involving parents in intervention, most commonly in providing home practice. On average, these tasks were recommended to be completed five times per week for 10 min. SLPs reported training parents using a range of training methods, most commonly providing opportunities for parents to observe the SLP conduct the intervention. SLPs' place of work and years of experience were associated with how they involved and trained parents in intervention. Most (95.8%) SLPs agreed or strongly agreed that family involvement is essential for intervention to be effective. Conclusion : Parent involvement and home practice appear to be intricately linked within intervention for phonology-based SSDs in Australia. More high-quality research is needed to understand how to best involve parents within clinical practice.